PENERAPAN SUPERVISI KLINIS UNTUK MENINGKATKAN KEMANDIRIAN DAN KETERAMPILAN MENGELOLA KELAS - Aspika Aspika (UNIVERSITAS BENGKULU, 2015)
Supervision is a management strategy that consists of a series of activities to ensure that the expected quality in the process of planning, implementation, and evaluation standards that haveditentukan.Praktek supervision is always changing along with the growing awareness of stakeholders to enhance the importance of improving the quality assurance mutu.Kesadaranakan related to the role, functions, and roles in the organization.Keyword: clinical supervision, independence, effective classroom management.